Penambahan Cendawan Pleurotus sp Pada Biochar Sekam Padi dan Tongkol Jagung untuk Stimulator di Lahan Berpasir - Rahim, Iradhatullah; Rusli, Rini; Ambar, Abdul Azis; Sukmawati, S; Suherman, S (Journal Galung Tropika, 2023)
Soybean is a protein source that is quite popular in Indonesia, so its demand is increasing every year. However, low production is one of the obstacles that causes these commodities to be imported from outside. One solution is to increase production by utilizing sandy land with low water holding capacity. This study aimed to determine the benefits of adding 2 types of biochar to the fungus isolate Pleurotus sp to increase yields on sandy soils. The study was arranged experimentally using a factorial design based on a randomized block design with 2 factors. The first factor was biochar treatment (J), including rice husk biochar (J1) and corncob biochar (J2). The second factor was the addition of Pleurotus sp fungus isolates, including without fungus (P1) and with fungus (P2). The results showed an increase in yield of pod weight, number of pods, number of seeds, and soybean production with the addition of Pleurotus sp to biochar. The increase in soybean yields using corn cob biochar added with Pleurotus was higher than rice husk biochar.